Media and the (im)permeability of public sphere to gender - Magalhães, Sara (2012)
We cannot continue to look at public sphere as a space of privileged, following an Habermasian logic. In this sense, an idealized definition of public sphere is created drawings upon equality opportunities and upon its intervenient rationalism, where the author clearly tries to retrieve Kantian sense of freedom. However, he focuses on male power holders and citizens’ participation. Moreover, public sphere is nowadays marked by multiple positions and actors that magnify its interactions. We are particularly interested on the uses of public sphere on media by its transformative capacity and the swell of a democratic space for every individuals. The breach of this sphere and its consequent fragmentation has functioned almost paradoxically: on one hand it allows subjects to position themselves and to take a stand but, on the other hand, it reinforces status quo, depriving other subjects from public sphere agency. This discursive (im)permeability carried out by the media against certain groups and individuals has raised debate in many areas. Feminist critique’s legacy has been extremely relevant to this public sphere conceptual evolution and reformulation, contributing to a more plural and equality conceptualization; one that is truly close to citizens and its idiosyncrasies. Feminist critique to Habermas’ bourgeois public sphere comes, first of all, from the recognition of women’s exclusion, as well as of other specific social groups, from figuring in society and from having an active part, therefore excluding them from democratic citizenship. The role of media, however, does not seem easy, as it is one of the privileged vehicles for information dissemination playing an important contribution to citizenship. Yet, in this junction there are diverse social actors that intend to enroll public decision-making. We know that public opinion is shaped mainly by parameters that prioritize some discourses over others, giving them more prominence and power. By highlighting these discourses, assigning greater emphasis to certain themes and people, media equally contribute to the formation and delimitation of public sphere boundaries. In this complex relationship established, and based on a critical feminist outlook, we intend with this paper to question the existence of a single public sphere or of several ones, and to question how far are mainstream media (im)permeable to emancipatory and resistance discourses. Finally, we will question, as well, how does public sphere and democracy notions articulate themselves with the increasing individualism promotion taking place in Western societies.